Symptoms associated with healthcare resource utilization in the setting of inflammatory bowel disease - Kaleb Bogale; Parth Maheshwari; Mitchell Kang; Venkata Subhash Gorrepati; Shannon Dalessio; Vonn Walter; August Stuart; Walter Koltun; Nana Bernasko; Andrew Tinsley; Emmanuelle D. Williams; Kofi Clarke; et al. (Scientific Reports, 2022)
Abstract Several symptoms have been connected to increased healthcare resource utilization (HRU) in the context of inflammatory bowel disease (IBD), including both Crohn’s disease (CD) and ulcerative colitis (UC). This study was designed to investigate the prevalence of IBD-associated symptoms and to determine whether any are independently associated with HRU. We undertook a retrospective analysis of data related to consecutive IBD patient encounters from a tertiary care referral center between 1/1/2015 and 8/31/2019. Demographics, clinical activity, endoscopic severity, IBD-related symptom scores, anxiety and depression scores, and other key clinical data were abstracted. Four hundred sixty-seven IBD patients [247f.: 220 m; 315 CD, 142 UC and 11 indeterminate colitis] were included in this study. The most common symptoms were fatigue (83.6%), fecal urgency (68.2%) and abdominal pain (63.5%). Fatigue, abdominal pain, anxiety or depression, corticosteroids, and opioids were each positively associated with HRU, while NSAID and mesalamine use were inversely associated on bivariate analysis. The only factor that demonstrated a statistically significant association with HRU in the whole cohort on multivariable analysis was abdominal pain. Abdominal pain is independently associated with HRU and should be specifically screened for in IBD patients to identify individuals at risk of undergoing expensive interventions. This study also reinforces the importance of optimizing diagnostic and therapeutic management of abdominal pain in IBD.